LEGISLATIVE AND LEGAL REGULATION OF ACTIVITY INTERNATIONAL FINANCIAL CENTER - Ju. N. Gusev (Модернизация, инновация, развитие, 2016)
What is needed: to improve legislative base of Russian financial markets taking into account the changes brought about by the global crisis; to form coordinated regulation system for financial markets; to create effective judicial system; to strengthen currency and financial cooperation with leading foreign trade partners of Russia.